The tale of Mr. Jeremy Fisher - Potter, Beatrix (London : Frederick Warne, 2002)
A frog fishing from his lily pad boat doesn't catch any fish, but one catches him.
Keywords: Frogs -- Juvenile fiction; Animal fiction